ENSURING INFORMATION SECURITY AS A COMPONENT OF NATIONAL SECURITY OF UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that the development of information technologies, on the one hand, leads to the emergence of more progressive, affordable, effective solutions in the domestic economy and social sphere, and on the other hand, it causes the emergence of new risks and problems for the national security of the state. Taking into account the current challenges and threats, we have singled out specific steps to ensure information security, namely the use of artificial intelligence capabilities in the course of ensuring information security; laying a reliable economic basis for the development of information technologies; provision of resource and infrastructural basis of information security of Ukraine; development of information competence and media education of the population.
Keywords: national security; information war; information security; information; information sovereignty